Endogenous product turnover and macroeconomic dynamics - Hamano, M; Zanetti, F (Elsevier, 2017)
This paper introduces endogenous product entry and exit based on creation and destruction of product variety in a general equilibrium model. Recessionary technology shocks induce exit of unprofitable products on impact, allocating resources towards more productive production lines. However, during the recovery phase, less productive production lines survive destruction, counteracting the original increase in productivity. The analysis shows that recoveries hinge on lower product destruction rather than higher product creation. We find that product heterogeneity and the persistence of technology shocks play a critical role for the cyclicality of product turnover. Endogenous product destruction is important to evaluate the effect of permanent policies of entry deregulation and subsidies aimed to stimulate the economy.